تحليل تنافسية قطاع السياحة والسفر في البلدان المغاربية الجزائر، تونس والمغرب حسب تقرير المنتدى الاقتصادي العالمي - دافوس - ماى، علي (جامعة العربي بن مهيدي - أم البواقي, 2018)
تهدف هذه الدراسة إلى تحليل تنافسية قطاع السياحة والسفر في البلدان المغاربية الجزائر، تونس والمغرب باستخدام مؤشرات تنافسية قطاع السياحة والسفر الصادرة عن تقارير المنتدى الاقتصادي العالمي بدافوس، وقد استخدمنا المنهج التحليلي الوصفي والمنهج المقارن، وخلصنا إلى أن هناك تباين في أداء مؤشرات تنافسية قطاع السياحة والسفر في البلدان محل الدراسة مع وجود أفضلية لهذه المؤشرات في كل من المغرب وتونس مقارنة بالجزائر.
The study aims to analyze the competitiveness of tourism and travel sector in Maghreb countries: Algeria, Tunisia and Morocco; through using the competitive indicators in the travel and tourism sector, issued by the World Economic Forum's reports, in Davos. We have used the both descriptive analytical and comparative approaches, we have concluded that there is a variation in the indicators performance of the sectors competitiveness tourism and travel in the countries studied, showing a salient advantage in Morocco and Tunisia compared to Algeria.
Keywords: التنافسية السياحية -- صناعة السياحة -- مؤشرات تنافسية قطاع السياحة والسفر -- البلدان المغاربية